Notes on the relative price of potatoes - Portocarrero, Gonzalo (1979)
The present work proposes to examine the evolution of the real prices of some food products in the Lima market for the period 53-74, emphasizing the case of the potato. it is about beginning to develop a line of research on the terms of rural-urban exchange and its trajectory in the recent past. It is undoubtedly a complex problem, but it is also decisive for understanding how such heterogeneous forms of production coexist and are articulated, that is, one of the basic characteristics of our economic process, which is uneven development.